“Jeg har jo oplevet det hele” - “Postrealisme” i franske romaner efter Claude Simon - Lund, Hans Peter (Passage - Tidsskrift for litteratur og kritik, 2012)
Hans Peter Lund: “‘I have seen it all’. Postrealism in French Novels after Claude Simon” From the 80s onward there has been a tendency in the French novel for letting a true story appear within the novel as autobiography or actual event. This article discusses texts from Claude Simon to Laurent Mauvignier, including François Bon, Boualem Sansal and others, and focuses on the fact that the material appears in novel-like constructions, as experienced, while it is also made the object of criticism.